Peran Musik Gereja Dalam Proses Pemulihan Korban Narkoba Di Panti Rehabilitasi Bunga Bakung Parepei, Remboken (Program Studi Musik Gereja, Fakultas Seni dan Ilmu Sosial Keagamaan, IAKN Manado, 2020)
Starting with trial and error, many young people who fall into drug abuse. he solution to deal with this social problem arose with set up various drug rehabilitation institutions for recovering patients physically, psychologically and spiritually. One method that is usually used is the method of music therapy as practiced by the Narcissus Narcotics Rehabilitation Institution in Parepei, Remboken.This study uses a qualitative method - Case Study with data collection methods through observation, interviews, and documentation. The results of the study found that the role of church music in the process of recovering narcotics victims was urgently needed seeing that most victims were Christians.The type of music used in the recovery process covers various genres of music, but only part of it is used because it is adapted to conditioned the victim. The process of recovery of victims through music went well and produced good results as well where the music was very necessary in recovery which was also balanced with other processes.